Gene Therapy Vector Encoding Neuropeptide Y and Its Receptor Y2 for Future Treatment of Epilepsy: Preclinical Data in Rats - Szczygieł, Julia Alicja; Danielsen, Kira Iben; Melin, Esbjörn; Rosenkranz, Søren Hofman; Pankratova, Stanislava; Ericsson, Annika; Agerman, Karin; Kokaia, Merab; Woldbye, David Paul Drucker (Frontiers in Molecular Neuroscience, 2020)
Gene therapy to treat pharmacoresistant temporal lobe epilepsy in humans is now being developed using an AAV vector (CG01) that encodes the combination of neuropeptide Y and its antiepileptic receptor Y2. With this in mind, the present study aimed to provide important preclinical data on the effects of CG01 on the duration of transgene expression, cellular tropism, and potential side effects on body weight and cognitive function. The CG01 vector was administered unilaterally into the dorsal and ventral hippocampus of adult male rats and expression of both transgenes was found to remain elevated without sign of decline at 6 months post-injection. CG01 appeared to mediate expression selectively in hippocampal neurons, without expression in astrocytes or oligodendrocytes. No effects were seen on body weight as well as on short- or long-term memory as revealed by testing in the Y-maze or Morris water maze tests. Thus these data show that unilateral CG01 vector treatment as future gene therapy in pharmacoresistant temporal lobe epilepsy patients should result in stable and long-term expression predominantly in neurons and be well tolerated without side effects on body weight and cognitive function.